2018
DOI: 10.3390/su10124858
|View full text |Cite
|
Sign up to set email alerts
|

Broadcasting Winter Wheat Can Increase Grain Yield without Reducing the Kernels per Spike and the Kernel Weight

Abstract: In North China, row spacing is the most common planting pattern used for winter wheat. Currently, there are three sowing and tillage methods for row spacing: rotary tillage sowing with straw return (RTS), subsoil tillage sowing with straw return (DTS), and no-tillage sowing with straw return (NTS). Recently, Hao proposed a new sowing pattern called uniform broadcast sowing with straw return (BSS) which could increase winter wheat yield. In this research, a field experiment was conducted during the growing seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…1). Delayed wheat sowing has been reported to hamper the initiation of both leaf and spikelet primordia, primarily due to water, nutrient and assimilate deficiencies, coupled with an overall shortened vegetative phase 40,41 . The reduction in the vegetative growth period, heads per square meter and LAI further elucidate the substantial decrease in yield components and final yield under delayed sowing (LS and VLS).…”
Section: Discussionmentioning
confidence: 95%
“…1). Delayed wheat sowing has been reported to hamper the initiation of both leaf and spikelet primordia, primarily due to water, nutrient and assimilate deficiencies, coupled with an overall shortened vegetative phase 40,41 . The reduction in the vegetative growth period, heads per square meter and LAI further elucidate the substantial decrease in yield components and final yield under delayed sowing (LS and VLS).…”
Section: Discussionmentioning
confidence: 95%
“…The grain yield of winter wheat is determined mainly by the number of spikes m −2 and, to a smaller extent, by the number of grains spike −1 and TGW [68][69][70]. Delayed sowing can potentially decrease the number of productive shoots and spikelet buds due to a lower number of leaves per unit area and a low leaf area index (LAI) [71][72][73][74]. In addition, delayed sowing shifts the phenological stages of winter wheat to periods with higher temperatures, which can induce considerable differences in grain formation (grains spike −1 and TGW) [75].…”
Section: Yield Componentsmentioning
confidence: 99%
“…In addition, Wang et al (2019) found that ploughing is a more suitable method of straw return (3.2 t•ha -1 ) than straw mulching in the rape-rice rotation pattern. According to a new planting pattern known as "broadcast sowing with straw return" has been adopted, grain yield improved without decreasing grains per spike and the 1000-grain weight (Zhai et al, 2018). Furthermore, straw return decreased the impact of higher grain yield by the co-application of mineral fertilizer or NPK fertilizer (Table S3).…”
Section: Crop Productionmentioning
confidence: 99%